Tamime and Robinson's Yoghurt - Science and Technology (3rd Edition) - Tamime, A. Y.; Robinson, R. K. (Richard Kenneth) (Woodhead Publishing Series in Food Science, Technology and Nutrition, 2007)
This book combines coverage of recent developments in scientific understanding with information about established best practices. It covers polysaccharide production by starter culture bacteria and its effects on gel structure, acid gel formation, and advances in the analysis of yoghurt in terms of its chemistry, rheology, and microbiology. The book explores advanced technology such as automation and mechanization, and details of clinical trials involving yoghurts. This new edition also discusses the new definition of the term yoghurt and the larger variety of gelled or viscous fermented milk products containing a wide range of cultures.